Despers Smokes 'em at Fiesta Final - Nero, Sean (Guardian)
Witco Desperadoes Steel Orchestra has walked away with the conventional band prize in Pan Trinbago's inaugural National Republic Pan Fiesta competition at the Queen's Park Savannah. Despers delivered a flawless rendition of "This Melody Sweet", composed by Winsford Des Vignes and arranged by Clive Bradley.
Keywords: Steel band music -- Competitions -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago; Steel bands (Music) -- Competitions -- Trinidad and Tobago